Snow angels eaudiobook Inspector vaara series, book 1. - Thompson, James (Inspector Vaara, 2014)
The first book of James Thompson's Inspector Vaara series won immediate critical acclaim for a sterling tale set in the brutal cold and soul-testing isolation of kaamos, Finland's two weeks of utter darkness. Even as the unrelenting winter conditions tighten their grip on the residents of the Lapland town, a lovely Somali movie star is found murdered, a racial slur cut into her chest. "Masterful."-Michael Connelly